OPTIMIZING WELL (WEB-ENHANCED LANGUAGE LEARNING) IN TEACHING READING - Avita Tri Rahayu; Lilies youlia Friatin; A.M. Surachmat (Universitas Galuh, 2020)
This study investigated on optimizing WELL (Web-Enhanced Language Learning) in teaching reading at the tenth grade of a Vocational High School in Cilacap. The purposes of the study were to investigate the teacher’s steps in optimizing WELL (Web-Enhanced Language Learning) in teaching reading and to figure out the students’ responses on optimizing WELL (Web-Enhanced Language Learning) in teaching reading. In this regard, a case study was applied as a research design in this study. Using purposive sample technique, the participants were an English teacher and twenty students at the tenth grade of a Vocational High School in Cilacap. Three instruments that were used are the observation, the interview, and the questionnaire. The findings indicated that there are thirteen steps of optimizing WELL which were used by the teacher in teaching reading to the students. The findings also indicated that the students gave their positive responses on optimizing WELL (Web-Enhanced Language Learning) in teaching reading to vocational school students. Key words: WELL (Web-Enhanced Language Learning), teaching reading, Vocational High School